New records of Palisada tenerrima and Hincksia mitchelliae from the Maltese Islands revealed by molecular analysis - BARTOLO, ANGELA G.; ZAMMIT, GABRIELLE; KÜPPER, FRITHJOF C. (Mediterranean Marine Science, 2022)
We report two new algal records from the Maltese islands: Hincksia mitchelliae (= Feldmannia mitchelliae) (Phaeophyceae) and Palisada tenerrima (Rhodophyceae). The former species was grown in culture from an Ulva sp. blade, while the latter was collected in the field. Our study employed an innovative integrative approach including morphological criteria as well as molecular analysis. DNA data and subsequent phylogenetic analysis of the COI gene and the rbcL plus RuBisCO spacer supported the separation of these two species from the closest-related congeners that had previously been reported from the Maltese islands.